Description of the larva of Mnesarete pudica (Hagen in Selys, 1853) (Odonata: Calopterygidae) and notes on known genera of South American Calopterygidae larvae - Guillermo-Ferreira, Rhainer; Bispo, Pitágoras C. (Zootaxa, 2012)
The final instar larva of Mnesarete pudica is described and illustrated based on reared specimens collected in Brazil. This species can be distinguished from others by presenting: a) five palpal and three premental setae; b) no posterodorsal hooks on abdominal segments; c) lateral spines only in S9-10. M. pudica is compared to other South American calopterygids and biological notes are presented.